Share it, Pin it, Tweet it: Effective Use of Social Media for Wildlife Rehabilitation - Nicholson, Amanda (Wildlife Rehabilitation Bulletin, 2013)
Flustered by Facebook®? Troubled by Twitter®? Perplexed by Pinterest®? This article provides an overview of the most effective social media tools today—with an emphasis on how nonprofit wildlife rehabilitation centers and organizations can use social media to support their wildlife work. Learn how to effectively and professionally share stories with others while garnering organizational support.